2021
DOI: 10.3390/jcm10071405
|View full text |Cite
|
Sign up to set email alerts
|

Application of Vibrational Spectroscopies in the Qualitative Analysis of Gingival Crevicular Fluid and Periodontal Ligament during Orthodontic Tooth Movement

Abstract: Optical vibrational techniques show a high potentiality in many biomedical fields for their characteristics of high sensitivity in revealing detailed information on composition, structure, and molecular interaction with reduced analysis time. In the last years, we have used these techniques for investigating gingival crevicular fluid (GCF) and periodontal ligament (PDL) during orthodontic tooth treatment. The analysis with Raman and infrared signals of GCF and PDL samples highlighted that different days of ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…The reported signals have been normalized assuming unitary the band area and the spectra have been deconvoluted in terms of Gaussian-Lorentzian mixed functions to outline the component modes. The red curve modes were assigned to α-helix secondary structure vibration, while the component at about 1620 cm −1 was assigned to 3 10 -helix and/or βsheet [6], and the modes in the 1660-1690 cm −1 range were ascribed to β-turn and β-sheet contributions as indicated in Figure 1b(i) [3,13]. The broad mode at about 1600 cm −1 was assigned to C=C stretching of amino acids [6].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The reported signals have been normalized assuming unitary the band area and the spectra have been deconvoluted in terms of Gaussian-Lorentzian mixed functions to outline the component modes. The red curve modes were assigned to α-helix secondary structure vibration, while the component at about 1620 cm −1 was assigned to 3 10 -helix and/or βsheet [6], and the modes in the 1660-1690 cm −1 range were ascribed to β-turn and β-sheet contributions as indicated in Figure 1b(i) [3,13]. The broad mode at about 1600 cm −1 was assigned to C=C stretching of amino acids [6].…”
Section: Resultsmentioning
confidence: 96%
“…The red curve modes were assigned to α-helix secondary structure vibration, while the component at about 1620 cm −1 was assigned to 3 10 -helix and/or βsheet [6], and the modes in the 1660-1690 cm −1 range were ascribed to β-turn and β-sheet contributions as indicated in Figure 1b(i) [3,13]. The broad mode at about 1600 cm −1 was assigned to C=C stretching of amino acids [6]. We have already observed that the relative intensity of the amide I band with respect to amide II band intensity decreases with the OTM times, indicating a protein rearrangement [4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman spectroscopy is commonly used for medical tasks among the optical methods used in bio-tissue research [ 10 , 11 ]. This method is also used in dentistry.…”
Section: Introductionmentioning
confidence: 99%